1994
DOI: 10.1002/ana.410350105
|View full text |Cite
|
Sign up to set email alerts
|

Concentric sclerosis (Baló): Morphometric and in situ hybridization study of lesions in six patients

Abstract: Brain tissues from 6 patients with concentric sclerosis (Baló) were examined by in situ hybridization, immunocytochemistry, morphometry, and histological methods. The patients were 24 to 48 years old and had progressive cerebral symptoms and signs that lasted 15 to 100 days. Large demyelinative lesions, most frequent in the frontal white matter, contained alternating bands of demyelinated and partly myelinated white matter that were arranged in concentric or mosaic patterns. In the areas of demyelination, axon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
60
2
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(67 citation statements)
references
References 19 publications
4
60
2
1
Order By: Relevance
“…3 However, more recently Moore et al have reported a case demonstrating lesions of the Baló type in the lumbar spinal cord as well as in the medulla oblongata 6 and Yao et al have described the histopathological findings of two patients with concurrent typical multiple sclerosis plaques and concentric sclerosis lesions and of another patient with these two lesion types in continuity. 2 The prior episode of left optic neuritis in our patient is consistent with the concept that Baló's concentric sclerosis is a variant of multiple sclerosis. In the present case, the diagnosis of Baló's concentric sclerosis was made on the basis of the second biopsy of the cerebral white matter lesion and supportive MRI findings.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…3 However, more recently Moore et al have reported a case demonstrating lesions of the Baló type in the lumbar spinal cord as well as in the medulla oblongata 6 and Yao et al have described the histopathological findings of two patients with concurrent typical multiple sclerosis plaques and concentric sclerosis lesions and of another patient with these two lesion types in continuity. 2 The prior episode of left optic neuritis in our patient is consistent with the concept that Baló's concentric sclerosis is a variant of multiple sclerosis. In the present case, the diagnosis of Baló's concentric sclerosis was made on the basis of the second biopsy of the cerebral white matter lesion and supportive MRI findings.…”
Section: Discussionsupporting
confidence: 90%
“…1,2 Baló suggested that 'encephalitis periaxialis concentrica' might represent a disease entity distinct from multiple sclerosis, partly because of the absence of spinal cord lesions. 3 However, more recently Moore et al have reported a case demonstrating lesions of the Baló type in the lumbar spinal cord as well as in the medulla oblongata 6 and Yao et al have described the histopathological findings of two patients with concurrent typical multiple sclerosis plaques and concentric sclerosis lesions and of another patient with these two lesion types in continuity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, our study has revealed that a proportion of Japanese MS patients possess DRB1*1502 but not DRB1*1501, and that TCLs recognizing the DRB1*1501-related MBP or PLP peptides can be efficiently generated from DRB1*1502 + patients (Ohashi et al, unpublished data). Furthermore, DRB1*1502 was found to be present in the vast majority of patients with concentric sclerosis (Baló's disease) (unpublished observation), which is probably a variant form of MS (24). Moreover, DRB1*1501 and DRB1*1502 differ only in the amino acid at position 86 of the DRβ chain (valine in DRB1*1501 and glycine in DRB1*1502) (25).…”
mentioning
confidence: 91%